Effects of Dietary Inositol Supplementation on Growth, Digestive Performance, Antioxidant Capacity, and Body Composition of Golden Pompano (Trachinotus ovatus) - Chen, Xu; Wang, Jun; Zhao, Wei (Frontiers in Physiology, 2022)
A 56-day culture experiment was performed to evaluate effects of inositol supplementation on growth, digestive performance, antioxidant capacity and body composition of golden pompano (Trachinotus ovatus). Five experimental diets (D1, D2, D3, D4 and D5) supplemented with 0, 150, 300, 600 and 1200 mg kg-1 inositol were formulated, respectively. Triplicate groups of 300 fish with an initial weight of (18.78 ± 0.21 g) and 15 seawater cages were used in the feeding experiment. Results indicated that the final body weight, weight gain rate, specific growth ratio and condition factor in fish fed with D3-D5 diets were significantly higher than those fed the D1 and D2 diets, and the highest values were detected in D3 diet treatment. The whole-body composition was not significantly affected by different experimental diets. Fish fed with D3-D5 diets showed higher activities of amylase, lipase and superoxide dismutase, and significantly higher than those fed with D1 and D2 diets. In contrast, fish fed with D3-D5 diets showed lower MDA content and significantly lower than those fed with D1 and D2 diets. The mRNA level of glutathione reductase in fish fed with D3 and D4 diets was significantly higher than those fed with D1, D2 and D5 diets. Likewise, the mRNA level of catalase significantly increased in the dietary inositol groups compared with the D1 group. In conclusion, the supplement of inositol not less than 300 mg kg-1 in the diet is indispensable to maintain the rapid growth and promote antioxidative capacity of T. ovatus.